Stres ekonomi dan kesehatan mental kalangan pekerja - Nasution, Helsa; Rahmadi, M. Agung; Mawar, Luthfiah; Sari, Milna (Jurnal Psikologi Poseidon, 2025)
Economic stress has become a significant concern in mental health research, particularly among the working population. This study aims to examine the impact of economic stress on workers' mental health through a comprehensive meta-analysis. Data were collected from various studies published over the past decade, focusing on economic stress, psychological distress, and coping strategies among employees. The results reveal a strong correlation between economic stress and mental health problems, with financial insecurity and job instability identified as key contributing factors. Furthermore, the study underscores the importance of effective coping strategies and social support in alleviating the adverse effects of economic stress. The findings provide practical insights for workplace interventions and inform policy recommendations.